Effect of left ventricular hypertrophy on the outcome of coronary artery bypass grafting - admin; Mohamed Magdy Abd Elalim; Amr Abdou Ettish; Wael Mohamed Elfeky; Mohamed Moustafa Abdelaal, Reda Biomy Basttawesy (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the relationship between left ventricular hypertrophy (LVH) and coronary artery bypass grafting (CABG) procedure especially on the early outcome during the first 6 months following surgical intervention Methods: This prospective cohort study included 82 patients with coronary artery disease indicating CABG. These patients were admitted, operated and followed -up in cardiothoracic surgery departments in the faculty of medicine, Kafrelsheikh university hospitals in the period from April 2019 till November 2021.The patients included in this study were divided into two groups according to presence or absence of left ventricular hypertrophy, Group I had 38 (46.34%) patients with LVH and Group 2 had 44 (53 .65%). patients without LVH. Results: The time to regain mechanical activity was longer (5.76±1.82) minutes in LVH patients (p <0.001). LVH group had a significantly longer period of mechanical ventilation 16.50±4.25 hours (p <0.001) compared to non LVH group which was 9.61±3.78 hours. Also, the mean duration of ICU stays in the LVH group compared to the non LVH group was 3.81±1.20 days versus 2.56±0.81 days respectively. The ICU follow up showed a statistically significant relationship of arrhythmias with LVH (p =0.022), infections (p =0.005) and wound infections (p<0.001). Conclusion: In patients undergoing CABG surgery, LVH has been associated with increased morbidity and poor outcome. Keywords: Hypertrophy, left ventricular, coronary artery disease, respiration, artificial, coronary artery bypass, morbidity, wound Infection, arrhythmias, cardiac DOI